Population projections for Sweden, Norway, Denmark, and Finland, 2015-2065 - Tarvainen, Kyösti (Bulletin of Geography. Socio-economic Series, 2018)
The ethnic and religious compositions of Nordic populations have been projected by Eurostat (Lanzieri, 2011), the Pew Research Center (2015), and Statistics Denmark (2015). These studies are updated and complemented in this paper. Lanzieri's consideration of the native population is supplemented by taking into account assimilation via marriages between natives and foreign-background persons. Immigration to Nordic countries increased significantly in 2015, but, on the other hand, immigration restrictions have been put in place. Therefore, there are no reliable estimates of future immigration. In this situation, the paper's "what if " projections, incorporating the average 2012-2014 net immigration level, serve as useful reference information. The projected demographic changes are similar in the four Nordic countries. The development is fastest in Sweden; in 2065, the share of the native population is to decrease to 49%, the Western population is projected to fall to 63%, and the Muslim population increase to 25%.